Hyperuricemia: An Early Marker for Severity of Illness in Sepsis - Sana R. Akbar; Dustin M. Long; Kashif Hussain; Ahmad Alhajhusain; Umair S. Ahmed; Hafiz I. Iqbal; Ailia W. Ali; Rachel Leonard; Cheryl Dalton (International Journal of Nephrology)
Background. Uric acid can acutely activate various inflammatory transcription factors. Since high levels of oxyradicals and lower antioxidant levels in septic patients are believed to result in multiorgan failure, uric acid levels could be used as a marker of oxidative stress and poor prognosis in patients with sepsis. Design. We conducted a prospective cohort study on Medical Intensive Care Unit (MICU) patients and hypothesized that elevated uric acid in patients with sepsis is predictive of greater morbidity. The primary end point was the correlation between hyperuricemia and the morbidity rate. Secondary end points were Acute Kidney Injury (AKI), mortality, Acute Respiratory Distress Syndrome (ARDS), and duration of stay. Results. We enrolled 144 patients. 54 (37.5%) had the primary end point of hyperuricemia. The overall morbidity rate was 85.2%. The probability of having hyperuricemia along with AKI was 68.5% and without AKI was 31.5%. Meanwhile the probability of having a uric acid value <7 mg/dL along with AKI was 18.9% and without AKI was 81.1% (p value < 0.0001). Conclusion. We report that elevated uric acid levels on arrival to the MICU in patients with sepsis are associated with poor prognosis. These patients are at an increased risk for AKI and ARDS.